Expression of thyroid hormone receptor during early development of the sea bream (Sparus aurata) - Llewellyn, Lynda (2014)
The thyroid hormones thyroxine (T4) and triiodothyronine (T3) are crucial to many aspects of vertebrate growth, development, and metabolism. They act through intracellular receptor proteins which act directly on target genes. Although the role of thyroid hormones in fish, especially in early development, is not well understood, thyroid hormones are passed to eggs by broodfish during spawning and are implicated in fish development.1,2 Sea bream (Sparus aurata) aquaculture has grown rapidly in importance in the European Community, particularly in southern Portugal. However, its further development is hindered by the high larval mortality rate and incidence of malformations. This work investigates the significance of thyroid hormones in sea bream development by cloning the thyroid hormone receptor (TR) and analyzing its expression during larval development.